Potensi Pemasukan Pemberdayaan Masyarakat Desa Melalui Pengembangan Pariwisata di Desa Pare Mas Kecamatan Jerowaru - Lau Ikbal Rangga Jati; M. Mario Bambang; Muhamad Zaril Gapari (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2024)
The potential of the tourism sector has a huge influence on the lives of local communities, such as the presence of traders selling various foods, drinks, and souvenirs, as well as providing transportation and various other services. This research aims to find out what the impact of community economic income through tourism is, and what are the supporting and inhibiting factors for tourism development in Pare Mas village. This type of research is descriptive qualitative which aims to explain or describe a situation, event, or object such as a person, or anything related to research. Analysis of data obtained based on data in the field, the analysis process has four stages, namely reduction, triangulation, data presentation, and verification/conclusion. Based on research conducted through interviews, observation, and documentation. The results of this research are (1) an Analysis of the impact of tourism in Pare Mas village on community income including (a) Business opportunities, and the impact of tourism in Pare Mas village in terms of community business opportunities to open business opportunities for them. This impact was felt directly by business people who previously did not work or housewives who had no income, as well as by people who previously worked but saw better opportunities at tourist attractions. (b) Infrastructure development, the existence of tourist attractions influences the development or improvement of better infrastructure, such as the construction of road access, prayer rooms, and bathrooms to attract tourists. (2) Supporting and inhibiting factors for tourism, (a) Supporting factors, support from the government by providing financial assistance every year, participation of Pokdarwis youth in Pare Mas village in conveying their ideas and aspirations, and community participation in managing tourist attractions in Pare Mas village. (b) Inhibiting factors, unfavorable weather which results in fewer visitors coming, promotions are still lacking, and human resources are still inadequate.